2013
DOI: 10.1007/s10493-013-9732-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Rhipicephalus (Boophilus) microplus and Haemaphysalis bispinosa ticks (Acari: Ixodidae) of North East India by ITS2 and 16S rDNA sequences and morphological analysis

Abstract: To investigate and identify the ticks prevalent in the North East part of India, scanning electron microscope (SEM) and DNA sequence of nuclear second internal transcribed spacer (ITS2) and mitochondrial 16S ribosomal DNA (rDNA) were used. Based on the morphological and molecular analysis, the ticks infesting cattle of North East India were found to be Rhipicephalus (Boophilus) microplus and Haemaphysalis bispinosa. ITS2 and 16S rDNA sequence from R. (B.) microplus and H. bispinosa were amplified using univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Subsequently, it is significant to develop more relevant characterization methods in order to differentiate subspecies and species while at the same time offers reliable and convenient technique. Molecular approach, mainly based on mitochondrial (mt) and ribosomal DNA (rDNA) fragments, has provided a complementary tool for accurate identification of ticks (Rumer et al 2011; Brahma et al 2014) and characterization of their pathogens (Cheng et al 2013). Furthermore, molecular identification can be the only technique when there are no other obvious means to match adults with immature stages (Frezal and Leblois 2008; Khera and Vohra 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it is significant to develop more relevant characterization methods in order to differentiate subspecies and species while at the same time offers reliable and convenient technique. Molecular approach, mainly based on mitochondrial (mt) and ribosomal DNA (rDNA) fragments, has provided a complementary tool for accurate identification of ticks (Rumer et al 2011; Brahma et al 2014) and characterization of their pathogens (Cheng et al 2013). Furthermore, molecular identification can be the only technique when there are no other obvious means to match adults with immature stages (Frezal and Leblois 2008; Khera and Vohra 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of 270 ticks examined in this study, 70 and 200 ticks were identified as R. microplus and H. bispinosa , respectively. Sequence analysis of the 16S rRNA gene amplified from B. bovis -positive ticks revealed 100 % identity (200 bp) with that of H. bispinosa reported in India (GenBank: KC853418- KC853420) [ 28 ]. Eight (4.0 %) H. bispinosa ticks collected from B. bovis- infected cattle in two farms (Farms 1 and 6) were positive using Bartonella gltA PCR assay.…”
Section: Resultsmentioning
confidence: 99%
“…R. microplus is a common tick in cattle while H. bispinosa tick has been reported to parasitize both cattle and goats [ 28 ]. B. bovis has been detected from 15.7 % of R. microplus ticks in Taiwan [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods, which focus on DNA-sequence differences, seems to be a better way to assess variation within and between species [3,4]. Because of the rapid evolution of the ITS regions, in comparison to coding regions, they are useful for distinguishing between closely related taxa [5] and have been used in characterization of different taxa of ticks [6][7][8][9][10].The hyper-variability of the second internal transcribed spacer (ITS 2) can also re ect intra-speci c differences allowing the separation even between different populations of the same species [11,12].…”
Section: Introductionmentioning
confidence: 99%